Food handlers' perceptions of the establishment of a healthy canteen at Jambi University - Puspita Sari; La Ode Reskiaddin; Rani Rizqi Dwi Larasati; Muhammad Ridwan; Vinna Rahayu Ningsih (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2022)
Background: In 2014 the POM Agency reported cases of food poisoning in various parts of Indonesia. One of these cases was caused by 15 cases of street food with 468 victims, and 1 case of poisoning due to catering services totaling 748 people. So, therefore destination study is for knowing the perception of handler food to the establishment of a healthy canteen at the University Jambi. Method: The research was conducted qualitatively using approach observation and Interview deep. The research subjects were 15 people consisting of 8 informants Main is a food handler and 7 person informant supporters, namely 3 Business Management Agency and 4 students. Result: The perception of food handlers on the establishment of a healthy canteen at Jambi University is quite good. The perception of vulnerability to the establishment of canteens at Jambi University is still not good. Likewise, the perception of barriers to the establishment of a healthy canteen at the University of Jambi is also still less than optimal. Then the readiness for the establishment of a healthy canteen at Jambi University is still inadequate and there are benefits from the establishment of a healthy canteen at Jambi University Conclusion: The perception of food handlers towards the establishment of a healthy canteen at Jambi University is quite good. However, perceptions of vulnerability, barriers, and readiness related to the establishment of a healthy canteen at Jambi University are still not optimal and there are benefits in establishing a healthy canteen at Jambi University. It is hoped that the canteen at Jambi University will make a policy regarding this matter, improve facilities and infrastructure and provide training to food handlers to increase knowledge about healthy canteens.